2001
DOI: 10.1246/bcsj.74.357
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Rotation Involving the Tetrahedral Carbon. LXIV. Barriers to Rotation of s-Alkyl Groups in 9-s-Alkyl-8,13-difluoro-1,4-dimethyl- and 1,2,3,4-tetrachloro-triptycenes

Abstract: 9-(3-Acetoxy-1-methylpropyl)-8,13-difluoro-1,4-dimethyltriptycene and 9-(1-methyl-2-propenyl)-8,13-difluoro-1,4-dimethyl- and 1,2,3,4-tetrachloro-triptycenes were prepared. Their barriers to internal rotation around the C(9)–C(alkyl) bonds were measured by the classical kinetics. The barrier was affected a little by the substituent, being ca. 25–26 kcal mol-1. Rotamer distributions in these compounds and possible causes for these indifferent barriers to rotation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We have found, through molecular modeling and experimental studies, that modified triptycene-derived compounds can be used to directly measure the strength of arene−arene interactions in the parallel-displaced configuration in organic solvents. Oki and co-workers pioneered the use of the triptycene molecular system in the study of weak molecular interactions. , No work related to π-stacking, however, has been reported using this system. The conformational equilibrium between the symmetrical anti form and the chiral syn forms in the triptycene molecular system ( 1 , Figure ) can be measured by low-temperature NMR spectroscopy by taking advantage of the slow rotation of the C9-benzyl carbon−carbon bond in compound 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We have found, through molecular modeling and experimental studies, that modified triptycene-derived compounds can be used to directly measure the strength of arene−arene interactions in the parallel-displaced configuration in organic solvents. Oki and co-workers pioneered the use of the triptycene molecular system in the study of weak molecular interactions. , No work related to π-stacking, however, has been reported using this system. The conformational equilibrium between the symmetrical anti form and the chiral syn forms in the triptycene molecular system ( 1 , Figure ) can be measured by low-temperature NMR spectroscopy by taking advantage of the slow rotation of the C9-benzyl carbon−carbon bond in compound 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For Trip(Me)−PIM, our results suggest that the methyl group undergoes reorientation, but that the reorientation is significantly more hindered than is typical for methyl groups in organic solids. Solution state NMR studies on triptycenes substituted with an isopropyl group at the bridgehead show that the activation energy for rotation about the C−CH(CH 3 ) 2 bond is in excess of 75 kJ mol −1 . Hence, it can be concluded that ethyl and isopropyl side-chains are unable to alter their conformation in order to occupy free volume and can be considered as part of the rigid framework of the PIM, whereas longer n- alkyl side-chains have sufficient conformational freedom to fill the free volume.…”
Section: Discussionmentioning
confidence: 99%
“…Returning to the opposite end of the folding molecule spectrum, minimal synthetic folding systems, such as the 'torsion balance' molecules developed by Oki and Wilcox have been extensively used for the study of non-covalent interactions. [52][53][54][55] Both of these systems have been exploited by other investigators. [56][57][58][59] Distinct foldamer signals in NMR spectra indicate that folding is a two-state event on the NMR timescale.…”
Section: Folding Moleculesmentioning
confidence: 99%